Eczema combined with diphyllobothriasis among representatives of one of the indigenous people of the North - A. V. Tsay; Yu. E. Rusak (Лечащий Врач, 2021)
A clinical case of eczema is presented in a representative of one of the smallest people of the North — the Selkup. The disease is associated with professional activity of the patient — the collection of wild plants.